The Effect of Ethanol Extract of Arabica Coffee (Coffea Arabica Linn) on the Number of Adult Pyramidal Pallium Zebrafish (Danio rerio) Neurons exposed to Stress Method UCS (Unpredictable Chronic Stress) - Muchamad Marwan; Zainuri Sabta Nugraha (Healthy-Mu Journal, 2021)
Chronic stress can have an adverse effect on behavior changes and damage to the pyramidal neurons of the brain. Pyramidal neurons of the brain play an important role in awareness, decision making, cognitive function, spatial memory formation and working memory. The effects of chlorogenic acid (CGA) found in arabica coffee can affect the improvement of cognitive function, working memory, and histology of brain pyramidal neurons. The content of chlorogenic acid (CGA) in coffee has active compounds that can maintain the number of brain pyramidal neurons due to stress. The aim of this study was to determine the effect of arabica coffee extract on the average number of brain pyramidal neurons exposed to UCS stress. The research method used was a post-test experimental study with controlled group design. A total of 24 adult zebrafish (3 months old) were divided into 4 groups. Four groups (KN, KP, K25, K50) were acclimatized (1 week) first, for groups K25 and K50 were given arabica coffee extract as much as 25mg / dl and 50 mg / dl for 4 days before inducing unpredictable chronic stress (UCS). The results of the study proved that the extra ethanol group of arabica coffee at a dose of 50 mg / dl could maintain the number of pyramidal neurons in zebrafish treated with modified UCS stress (P <0.05). In conclusion, giving ethanol extract of arabica coffee at a dose of 50 mg / dl has a neuroprotectant effect on zebrafish exposed to UCS stress.